Landing - Donoghue, Emma 1969- (Harcourt, 2007)
Over the course of a year, the lives of two women--Sile, a flight attendant and world traveler, and Jude, a young archivist stubbornly attached to the town of Ireland, Ontario--intersect, in a story that reveals the joys and sorrows of a long-distance relationship.
Keywords: Long-distance relationships -- Fiction; Lesbians -- Fiction; Flight attendants -- Fiction; Women archivists -- Fiction; Dublin (Ireland) -- Fiction; Ontario -- Fiction; Love stories; Humorous fiction